Study of an Efficient and Environmentally Friendly Germanium-Based CsGeI3 Perovskite Structure For Single and Double Solar Cells - Arbouz, Hayat (International Journal of Computational and Experimental Science and Engineering, 2024)
This work deals with the simulation and optimization of a single perovskite solar cell based on the lead-free, inorganic perovskite absorber CsGeI3 with a bandgap energy of 1.6 eV. An appropriate simulation model was designed on the basis of the physical properties employed and carefully selected. Firstly, the study demonstrated the role of increasing the bulk defect density of the absorber as well as the interface defect density at the boundaries between the absorber and the carrier transport layers on increasing the photo-generated carrier recombination velocity, causing the collapse of the solar cell performance. The effect of layer thickness on photovoltaic parameters was also investigated. Next, various combinations of ETL and HTL electron and hole transport materials, with different bandgap alignments with the absorber were studied. The performance of the different structures was used to determine the optimum structure for obtaining the best results. An efficiency of 15.9% was obtained with the ETL-SnO2 /CsGeI3/HTL- SrCu2O2 architecture. Finally, the optimized structure was simulated in a 2T-tandem configuration in combination with the 1.3 eV-CsSnI3 based solar sub-cell. It was found that the efficiency could reach 25%. The aim of this work is to develop an efficient, lead-free and stable perovskite cell structure that could replace its hybrid perovskite counterpart and be used as a performing sub-cell in a tandem structure.